Measuring Practicing Clinicians’ Information Literacy - Dixon, Brian E; Barboza, Katherine; Jensen, Ashley E; Bennett, Katelyn J; Sherman, Scott E; Schwartz, Mark D (Applied Clinical Informatics, 2017)
Background: As healthcare moves towards technology-driven population health management, clinicians must adopt complex digital platforms to access health information and document care. Objectives: This study explored information literacy, a set of skills required to effectively navigate population health information systems, among primary care providers in one Veterans’ Affairs (VA) medical center.Methods: Information literacy was assessed during an 8-month randomized trial that tested a population health (panel) management intervention. Providers were asked about their use and comfort with two VA digital tools for panel management at baseline, 16 weeks, and post-intervention. An 8-item scale (range 0-40) was used to measure information literacy (Cronbach’s α=0.84). Scores between study arms and provider types were compared using paired t-tests and ANOVAs. Associations between self-reported digital tool use and information literacy were measured via Pearson’s correlations.Results: Providers showed moderate levels of information literacy (M= 27.4, SD 6.5). There were no significant differences in mean information literacy between physicians (M=26.4, SD 6.7) and nurses (M=30.5, SD 5.2, p=0.57 for difference), or between intervention (M=28.4, SD 6.5) and control groups (M=25.1, SD 6.2, p=0.12 for difference). Information literacy was correlated with higher rates of self-reported information system usage (r=0.547, p=0.001). Clinicians identified data access, accuracy, and interpretability as potential information literacy barriers.Conclusions: While exploratory in nature, cautioning generalizability, the study suggests that measuring and improving clinicians’ information literacy may play a significant role in the implementation and use of digital information tools, as these tools are rapidly being deployed to enhance communication among care teams, improve health care outcomes, and reduce overall costs.
Keywords: Information systems; information literacy; health services needs and demand; informatics; human engineering or usability